2021
DOI: 10.3168/jds.2020-19674
|View full text |Cite
|
Sign up to set email alerts
|

Maternal supplementation with cobalt sources, folic acid, and rumen-protected methionine and its effects on molecular and functional correlates of the immune system in neonatal Holstein calves

Abstract: Calves born to multiparous Holstein cows fed during the last 30 d of pregnancy 2 different cobalt sources [cobalt glucoheptonate (CoPro) or cobalt pectin (CoPectin)], folic acid (FOA), and rumenprotected methionine (RPM) were used to study neonatal immune responses after ex vivo lipopolysaccharide (LPS) challenge. Groups were (n = 12 calves/ group) CoPro, FOA+CoPro, FOA+CoPectin, and FOA+CoPectin+RPM. Calves were weighed at birth and blood collected at birth (before colostrum), 21 d of age, and 42 d of age (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Using previously established centrifugation protocols (Roth and Kaeberle 1981 ), we isolated Peripheral Blood Mononuclear Cells (PBMC), and PMNs. After staining our fractionated PBMC or PMN cell fractions using an anti- bovine granulocyte monoclonal antibody (GR-1) (Etchevers et al 2023 ; Lietaer et al 2021 ; Lopes et al 2021 ; Oliveira et al 2020 ), we found that our PMN fraction was viable, and had a PMN identity, as anti-GR-1 reactivity was very high in all of the PMN cells, but few of the PBMC cells (Fig. 1 A).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Using previously established centrifugation protocols (Roth and Kaeberle 1981 ), we isolated Peripheral Blood Mononuclear Cells (PBMC), and PMNs. After staining our fractionated PBMC or PMN cell fractions using an anti- bovine granulocyte monoclonal antibody (GR-1) (Etchevers et al 2023 ; Lietaer et al 2021 ; Lopes et al 2021 ; Oliveira et al 2020 ), we found that our PMN fraction was viable, and had a PMN identity, as anti-GR-1 reactivity was very high in all of the PMN cells, but few of the PBMC cells (Fig. 1 A).…”
Section: Resultsmentioning
confidence: 85%
“…Isolated leukocytes were stained with anti- bovine GR-1 antibody to confirm PMN identity, as previously described (Etchevers et al 2023 ; Lietaer et al 2021 ; Lopes et al 2021 ; Oliveira et al 2020 ). Briefly, cells were stained with mouse anti-bovine granulocyte (GR-1) monoclonal IgM primary antibody (clone-CH138A, Kingfisher Biotech), or isotype control (clone-COLIS52A2, Kingfisher Biotech) at a concentration of 1.0 ug/mL, followed by a FITC goat anti-mouse IgM polyclonal secondary antibody (ThermoFisher) at a concentration of 1.5 ug/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Peripartal dairy cows are often in a state of negative energy balance (NEB) due to the increase in energy demands and the decrease of DMI (Lopreiato et al, 2020;Bucktrout et al, 2021;Lopes et al, 2021). Severe NEB leads to metabolic disorders including ketosis.…”
Section: Introductionmentioning
confidence: 99%
“…Trace elements affect the concentration of volatile fatty acids, the pH of the rumen, methane formation, and fermentation in the rumen of ruminants [12]. Adding cobalt to animal diets improves the digestibility of feed fiber in the rumen [13], increases the immunity of animals [14], and increases the concentration of B12 vitamin [15].…”
Section: Introductionmentioning
confidence: 99%